Inconsistency arguments still do not matter. Issue 7 (14th July 2021) - Blackshaw, Bruce Philip; Colgrove, Nicholas; Rodger, Daniel
Abstract : William Simkulet has recently criticised Colgrove et al 's defence against what they have called inconsistency arguments—arguments that claim opponents of abortion (OAs) act in ways inconsistent with their underlying beliefs about human fetuses (eg, that human fetuses are persons at conception). Colgrove et al presented three objections to inconsistency arguments, which Simkulet argues are unconvincing. Further, he maintains that OAs who hold that the fetus is a person at conception fail to act on important issues such as the plight of frozen embryos, poverty and spontaneous abortion. Thus, they are morally negligent. In response, we argue that Simkulet has targeted a very narrow group of OAs, and so his criticisms are inapplicable to most OAs. We then explain why his responses to each of Colgrove et al's objections do not succeed, even for this restricted group. Finally, we note that Simkulet fails to provide evidence for his claims regarding OAs' supposed failures to act, and we show that OAs veritably do invest resources into these important issues. We conclude that Colgrove et al 's reasons for rejecting inconsistency arguments (en masse) remain intact.